Topology optimization of fins for energy storage tank with phase change material. (1st February 2020) - Zhao, Ming; Tian, Yang; Hu, Mingyu; Zhang, Fengming; Yang, Mo
Abstract: Six models based on different fin configuration of the energy storage tank with phase change material were established. The fin structure of model 3 is designed by topology optimization method. The thermal storage and release process of the six models were calculated by numerical simulation method. The results show that according to the thermal storage and release process of model 2, fin of model 3 is designed by topology optimization method. Thermal storage and release process of model 3 are both satisfactory agreement with the topology optimization results. Uniformity of temperature and liquid fraction is also significantly improved. Moreover, the model 3 can reduce the thermal storage time by 70% compared to model 2 and reduce the thermal release time by 81%. Furthermore, by comparison with all the 6 models, model 3 with the fin design based on the topology optimization method is found to have the significant advantages of less fins, metal saving, and low weight.